2010
DOI: 10.1007/s10597-010-9331-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Client Services (ECS): A Measure of Treatment Satisfaction for People with Chronic Mental Illnesses

Abstract: This article describes the development and psychometric assessment of the Evaluation of Client Services (ECS) measure of treatment satisfaction for people with chronic mental illnesses in community treatment settings. The ECS, a 20-item instrument, was validated in a sample of 184 individuals receiving outpatient mental health treatment in New York City. The four dimensions of the ECS, (1) treatment management and treatment outcome, (2) treatment relationship, (3) communication and information exchange, and (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Quality of FCC was significantly related to both patients' and family caregivers' perception of family functioning. Berghofer, Castille, and Link () speculated that patients who are satisfied with cooperation from mental healthcare providers are more likely to adhere to their recommended treatments. Moreover, satisfaction with mental health treatment (e.g., family‐oriented mental healthcare services) may assist family caregivers in reframing mental illness in a positive light and ultimately facilitate adaptive family functioning (Crowe & Lyness, ).…”
Section: Discussionmentioning
confidence: 99%
“…Quality of FCC was significantly related to both patients' and family caregivers' perception of family functioning. Berghofer, Castille, and Link () speculated that patients who are satisfied with cooperation from mental healthcare providers are more likely to adhere to their recommended treatments. Moreover, satisfaction with mental health treatment (e.g., family‐oriented mental healthcare services) may assist family caregivers in reframing mental illness in a positive light and ultimately facilitate adaptive family functioning (Crowe & Lyness, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the factors associated with service user satisfaction with mental health services has tended to explore satisfaction with inpatient or outpatient services (Berghofer, Castille, & Link, ; Gebhardt, Wolak, & Huber, ; Haahr et al ., ; Richardson, Katsakou, & Priebe, ), rather than psychological therapy specifically. Conflicting findings have been reported in relation to demographic factors, initial symptom severity, and clinical outcomes, whereas satisfaction is more consistently associated with service users’ ratings of their quality of life and their therapeutic relationship with the treating team (e.g., Berghofer et al ., ; Eklund & Hansson, ; Gebhardt et al ., ; Holcomb, Parker, Leong, Thiele, & Higdon, ; Prince, ; Ruggeri, Gater, Bisoffi, Barbui, & Tansella, ; Smith et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients’ perception of service characteristics such as adequacy of staff, treatment suitability, as well as quantity and quality of information received (that is, aspects that go beyond the patient’s satisfaction with medication) may play important roles in patient quality of life. Involving the patients’ subjective perspective in the treatment process has been suggested to promote service effectiveness [ 30 33 ]. Consistent with these ideas, quality of life improvement has been reported from patients with higher service satisfaction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst one study indicated a positive relationship in a sample of outpatients [ 36 ], another two studies did not find such an association for the same treatment context [ 36 ] or for inpatients [ 37 ]. The majority of the studies have explored the relationship between service satisfaction and the subjective quality of life domain reporting a consistent relationship for outpatients [ 30 , 38 41 ], inpatients [ 37 , 42 43 ], or patients in both treatment contexts [ 44 ]. Typically, overall quality of life (i.e., based on composite scores from subjective and objective quality of life domains) has been found to be positively related to service satisfaction [ 45 49 ].…”
Section: Introductionmentioning
confidence: 99%